2002
DOI: 10.1046/j.0007-1331.2001.00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Fos Immunoreactivity in the Diagonal Band and the Perinuclear Zone of the Supraoptic Nucleus after Hypertension and Hypervolaemia in Unanaesthetized Rats

Abstract: We used Fos immunocytochemistry to study the effects of hypertension and hypervolaemia on neurones in the diagonal band of Broca and the perinuclear zone of the supraoptic nucleus, two nuclei that are both involved in the baroreceptor regulation of vasopressin neurones in the supraoptic nucleus. In addition, we used sino-aortic denervation to examine the role of arterial baroreceptors in the response to these haemodynamic changes. Sham-operated and sino-aortic denervated rats were infused with phenylephrine su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 30 publications
(107 reference statements)
1
12
0
Order By: Relevance
“…Enhanced ZsYellow1 expression was obtained by using an optimized c-fos promoter, leading to 16-fold increases in mRNA accumulation via activation of the cAMP-responsive (CRE) and the serum-responsive (SRE) promoter elements (Susini et al, 2000). C-fos expression has been shown to significantly increase in the CNS as a response to various physiological stimuli (Tian and Bishop, 2002) (Lin et al, 2011) (Curran and Morgan, 1995; Dampney et al, 1995; Cunningham et al, 2002). Previous studies obtained in vitro have shown that c-fos mRNA expression can be observed within five minutes following stimulation, and peaks 10-20 minutes after stimulation (Greenberg and Ziff, 1984; Flavell and Greenberg, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced ZsYellow1 expression was obtained by using an optimized c-fos promoter, leading to 16-fold increases in mRNA accumulation via activation of the cAMP-responsive (CRE) and the serum-responsive (SRE) promoter elements (Susini et al, 2000). C-fos expression has been shown to significantly increase in the CNS as a response to various physiological stimuli (Tian and Bishop, 2002) (Lin et al, 2011) (Curran and Morgan, 1995; Dampney et al, 1995; Cunningham et al, 2002). Previous studies obtained in vitro have shown that c-fos mRNA expression can be observed within five minutes following stimulation, and peaks 10-20 minutes after stimulation (Greenberg and Ziff, 1984; Flavell and Greenberg, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…physiological grounds, the Ov has been implicated in a wide variety of adaptative responses (Herman and Cullinan, 1997;Day et al, 1999Day et al, , 2001Cunningham et al, 2002;Engström et al, 2003;Amir et al, 2004;Nakagawa et al, 2005). Notably, some neurons and fibers in the Ov are immunnoreactive to CRF (CRF-I; and to CRF-binding.protein (Peto et al, 1999), respectively.…”
mentioning
confidence: 99%
“…Regions of interest were identified using the rat brain stereotaxic atlas of Paxinos and Watson (1986). Three to six images were taken from each region for each animal bilaterally as previously described (Cunningham et al, 2002(Cunningham et al, , 2007Howe et al, 2004;Ji et al, 2005). The number of c-Fos or DFosB positive cells were recorded for each image and averaged for each animal.…”
Section: Fos and Dfosb Immunohistochemistrymentioning
confidence: 99%
“…The number of c-Fos or DFosB positive cells were recorded for each image and averaged for each animal. Counts were generated by observers who were blind to the treatment condition associated with the images (Cunningham et al, 2002(Cunningham et al, , 2007Howe et al, 2004;Ji et al, 2005).…”
Section: Fos and Dfosb Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation